(untitled) (Journal of Mechanical Engineering, 2018)
Flow control is a significant topic of research in the field of aviation. Researchers in this field are continuously trying their best to find various flow control strategies in order to extract aerodynamic benefits by applying them. Applying moving surface at the leading edge of aerofoil is a type of strategy among the various types of active flow control strategies. In the present research work a rotating cylinder is added on the leading edge of the aerofoil as a moving surface in order to control the flow over its surface. The moving surface boundary layer control is applied to NACA 0018 airfoil for investigating its aerodynamic benefits and effectiveness. The moving surface is created by rotating a smooth cylinder at the leading edge of the aerofoil. The peripheral velocity of the cylinder injects momentum to the upper surface boundary layer of the aerofoil and thus delays its separation. This results in the gain in both the maximum lift coefficient and the stall angle. The work has been done at four different Reynolds Number i.e., at Re = 1.4 X 10^5, 1.85 X 10^5, 2.3 X 10^5, 2.8 X 10^5 at different angles of attack.